Analisis Work Engagement Karyawan Frontline High-Contact dan Low –Contact Industri Jasa di Jakarta dan Tangerang - Asan, Sucipto; Judith, Juana (Universitas Mercu Buana, 2020)
ABSTRACT :Work engagement in frontline employees play an important role that will effect and the capability of the organization in serving its customer. This research was to examine whether there were differences in the influence of Service Climate, Job Satisfaction and Affective Commitment on Work Engagement in High-Contact and Low Contact frontline employees in Jakarta and Tangerang. And whether there were influences of Work Engagement on Adaptability behavior as well as Career Commitment among High Contact and Low Contact frontline employees in Jakarta and Tangerang. The author found there were almost no differences among High Contact and Low Contact frontline employees except on the Job Satisfaction, where there was no significant influence toward Work Engagement in frontline low-contact employee which was in contrast with the frontline High-Contact employee. This research will enrich the discourse on the relationship between Job Satisfaction and Work Engagement. This finding provides empirical evidence on a limited scale that in certain segmentation, especially for low contact workers, job satisfaction did not have a positive influence on Work Engagement. ABSTRAK:Work Engagement (pikiran dan emosi positif bekerja) di karyawan garis depan (frontline) memainkan peran penting yang akan mempengaruhi dan kemampuan organisasi dalam melayani pelanggannya. Penelitian ini untuk menguji apakah ada perbedaan pengaruh Iklim Layanan, Kepuasan Kerja dan Komitmen Afektif terhadap Work Engagement pada karyawan frontline High-Contact dan Low-Contact di Jakarta dan Tangerang. Dan apakah ada pengaruh Work Engagement terhadap perilaku Adaptabilitas serta Komitmen Karir di antara karyawan frontline High-Contact dan Low-Contact di Jakarta dan Tangerang. Penulis menemukan hampir tidak ada perbedaan antara karyawan frontline High-Contact dan Low-Contact kecuali pada Kepuasan Kerja, di mana tidak ada pengaruh yang signifikan terhadap Keterlibatan Kerja di karyawan kontak rendah di garis depan yang berbeda dengan karyawan frontline High-Contact. Penelitian ini akan memperkaya wacana tentang hubungan antara Kepuasan Kerja dan Work Engagement. Temuan ini memberikan bukti empiris pada skala terbatas bahwa dalam segmentasi tertentu, terutama untuk pekerja Low-Contact , kepuasan kerja tidak memiliki pengaruh positif pada Work Engagement.